KONSTRUKSI AKAD DALAM PENGEMBANGAN PRODUK PERBANKAN SYARIAH DI INDONESIA - Ghofur, Ruslan Abdul (Universitas Islam Negeri Raden Intan Lampung, 2015)
Abstract: The Construction of Akad (Contracts) to Develop of Islamic Banking Products in Indonesia. The principle of flexibility in business transactions in Islam is, in fact, a strategic solution to face with the complexity of economic problems and public demands of Islamic banking role. Unfortunately, the banking practitioners understand the principle narrowly which results in a limited space for Islamic bankings to meet the needs of the community. This paper suggests strategic steps to develop Islamic banking products while still remain bound by the principles and values of Islam. The steps are : first, reformulating the concepts of contracts in Islamic banking; second, optimizing the role of the Sharia Supervisory Board (DPS); Third, the empowering potency for socio-economic development. If these three steps are performed, the Islamic banking is believed to be able to meet the demands of society in achieving social welfare. Abstrak: Konstruksi Akad dalam Pengembangan Produk Perbankan Syariah di Indonesia. Prinsip keleluasan bermuamalah dalam Islam merupakan modal utama untuk menghadapi kompleksitas permasalahan ekonomi serta besarnya tuntutan masyarakat akan peran perbankan syariah. Sayangnya, para praktisi perbankan sering memahami prinsip bertransaksi secara sempit sehingga berdampak pada terbatasnya ruang gerak perbankan syariah dalam memenuhi kebutuhan masyarakat. Tulisan ini mengetengahkan langkah-langkah strategis dalam pengembangan produk perbankan syariah dengan tetap terikat oleh prinsip dan nilai-nilai syar’i. Langkah-langkah tersebut di antaranya adalah: pertama, rekonsepsi tentang pemahaman akad-akad pada bank syariah; kedua, optimalisasi peran Dewan Pengawas Syariah (DPS); ketiga, pemberdayaan potensi sosial ekonomi masyarakat. Jika ketiga langkah tersebut dilakukan maka perbankan syariah diyakini akan mampu memenuhi tuntutan masyarakat dalam mewujudkan kesejahteraan sosial.